BETWEEN MARKETING AND ONLINE SOFT DIPLOMACY: ASSESSING SOUTH KOREAN HEALTH AND BEAUTY PRODUCTS EXPANSIONS IN INDONESIA - Darynaufal Mulyaman; Gradiola Stacie Oley (Jurnal Kajian Wilayah, 2020)
This study explains how South Korean companies’ innovations, especially the ones which are running in beauty and health industries, have positive impacts to South Korean economy. It brings out some questions such as: isthis a kind of new soft power method? With its enormous online network, how and why South Korean health and beauty products become so imminent in Indonesia? This study argues that a successful soft power strategy needsa co-opted measure in distribution and cyber world is vast place that could benefit a country that knows how touse it well. Furthermore, the collected data are literature studies from relevant sources, such as press releases andgovernment publications, from November 2019 to January 2020.